Effect of altering the whey protein/casein ratio on quality properties of ice cream - Muhammad Azeem Ur Rehman Alvi; Joy Ikedichi Agbawodike; Andrea G. Soler-Sánchez; Sergio I. Martínez-Monteagudo (International Journal of Food Properties)
The effect of altering the protein ratio (whey protein/casein) on the rheology, overrun, hardness, meltdown, and shape retention of ice creams was evaluated. Five protein ratios (13/87, 20/80, 33/67, 45/55, and 54/46) were tested in formulations containing 4.5% total protein, 13% total fat, and 42% total solids. Ice creams containing more caseins (13/87 and 20/80) displayed higher overrun values (56.21 ± 2.45 and 38.14 ± 4.61%) and lower hardness (52.13 ± 2.25 and 58.14 ± 2.87 N), while ice creams containing more whey protein led to harder texture (75.18 ± 3.47 N) and lower overrun (20.83 ± 3.10%). Altering the protein ratio substantially changed the onset of meltdown, where a 1.8-fold delay was obtained in 20/80 ice creams compared with the 54/46 ice creams. Moreover, the meltdown behavior, a dimensionless response, successfully mapped the ice creams containing different protein ratios based on their hardness and meltdown curve.